Design of treatment trials for functional gastrointestinal disorders. (1st September 1999) - van Zanten, S J O Veldhuyzen; Talley, N J; Bytzer, P; Klein, K B; Whorwell, P J; Zinsmeister, A R
Abstract : Until recently many clinical trials of functional gastrointestinal disorders (FGIDs) suffered from important weaknesses in trial design, study execution, and data analysis. This makes it difficult to determine whether truly efficacious therapies exist for these disorders. One of the important methodologic problems is the absence of validated outcome measures and lack of consensus among stakeholders on how to measure outcome. Currently much of the effort is being put into the development of validated outcome measures for several of the FGIDs. The randomized, controlled trial with parallel groups is the design of choice. In this report, guidelines are given for the basic architecture of intervention studies of FGIDs. Further studies on design issues are required to ensure the recommendations will become evidence based in the future.